English response to Goethe, 1824-1865 - Smith, D; Smith, David Francis (1982)
This thesis, concerned with critical response and not with influence, examines British opinions of Goethe's: works and life as expressed in review articles, prefaces- to translations, creative works, memoirs and correspondence, and biographical studies. The period is divided into two sections, before and after 1845, and in each section there is. one chapter on a Goethe-critic of outstanding importance (Carlyle and G.H. Lewes, respectively), followed by two chapters on the general critical response. The aim is to discover types of response to Goethe and to show how they are related to each other. Chapter one examines the successive stages, of Carlyle's intellectual relationship to Goethe, and shows the unbalanced and essentially transient nature of his adherence. Chapters two and three deal respectively with reception of individual works by Goethe and with more general opinions, showing a rapid increase in the interest and respect inspired by Goethe in Britain, but also a strong distrust in many quarters, normally centred on the moral deficiencies of Goethe's works and life. Chapter four studies in detail G.H. Lewes's intellectual development up to the 1850s, and connects the various features of his biography of Goethe (1855) with other aspects of his thought. Chapters five and six consider separately negative and positive attitudes to Goethe from 1846 to 1865. Moralistic distrust persists among an older generation of critics, but the general tendency is more towards adverse criticism on artistic grounds and unworried pity for an incomplete moral character, or appreciation of the freshness and healthiness of Goethe's art and an admiration of the breadth of his wisdom which stops short of the messianic claims for Goethe as a potential moral and religious leader made by Carlyle and a few others inspired by Carlyle.